Institutional Impact of EVAR's Incorporation in the Treatment of Abdominal Aortic Aneurysm: a 12 Years' Experience Analysis - Machado, R. (2016)
Introduction: Endovascular aneurysm repair (EVAR) was introduced as a less aggressive treatment of abdominal aortic aneurysms (AAA) for patients ineligible for open repair (OR). Objective: To analyze EVAR's incorporation impact in the treatment of infra-renal abdominal aortic aneurysms in our institution. Methods: A retrospective study of the patients with diagnostic of infra-renal AAA treated between December 2001 and December 2013 was performed. The choice between EVAR and OR was based on surgeon's experience, considering patient clinical risk and aneurysm's anatomical features. Patients treated by EVAR and by OR were analyzed. In each group, patient's and aneurysm's characteristics, surgical and anesthesia times, cost, transfusion rate, intraoperative complications, hospital stay, mortality and re-intervention rates and survival curves were evaluated. Results: The mean age, all forms of heart disease and chronic renal failure were more common in EVAR group. Blood transfusion, surgical and anesthesia times and mean hospital stay were higher for OR. Intraoperative complications rate was higher for endovascular aneurysm repair, overall during hospitalization complication rate was higher for open repair. The average cost in endovascular aneurysm repair was 1448.3€ higher. Re-interventions rates within 30 days and late re-intervention were 4.1% and 11.7% for endovascular aneurysm repair versus 13.7% and 10.6% for open repair. Conclusions: Two different groups were treated by two different techniques. The individualized treatment choice allows to achieve a mortality of 2.7%. Age ≥80 years influences survival curve in OR group and ASA ≥IV in EVAR group. We believe EVAR's incorporation improved the results of OR itself. Patients with more comorbidities were treated by endovascular aneurysm repair, decreasing those excluded from treatment. Late reinterventions were similar for both techniques.